2005
DOI: 10.1111/j.1469-8986.2005.00279.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathic traits and autonomic responding to concealed information in a prison sample

Abstract: We examined the role of psychopathic traits on physiological responding during a concealed information polygraph test among prison inmates (n = 40). The Psychopathic Personality Inventory (Lilienfeld & Andrews, 1996) was used to assess psychopathic traits. Cardiac, electrodermal, and respiratory responses were measured while participants were presented with personal and control names and asked to conceal recognition of personal information. We first piloted the present concealed information test in a sample of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 42 publications
1
33
0
Order By: Relevance
“…That is, the correct test items elicit a modest (1-5 bpm) and immediate (onset latency 1-3 s after stimulus onset) heart rate deceleration that is greater than that observed to the incorrect items. This pattern replicates previous research using the silent condition (Verschuere et al 2004(Verschuere et al , 2005(Verschuere et al , 2007b. Heart rate deceleration can result from parasympathetic activation or sympathetic withdrawal.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…That is, the correct test items elicit a modest (1-5 bpm) and immediate (onset latency 1-3 s after stimulus onset) heart rate deceleration that is greater than that observed to the incorrect items. This pattern replicates previous research using the silent condition (Verschuere et al 2004(Verschuere et al , 2005(Verschuere et al , 2007b. Heart rate deceleration can result from parasympathetic activation or sympathetic withdrawal.…”
Section: Discussionsupporting
confidence: 86%
“…Verschuere et al (2004), for example, presented 36 ''guilty'' undergraduates with mock crime and control pictures with no requirement to give an overt response. Results showed not an initial acceleration but instead an immediate heart rate deceleration to the correct items (see also, Verschuere et al 2005). In the present study, we directly tested the hypothesis that verbalization explains the initial heart rate acceleration that has been observed in the concealed information test.…”
Section: Introductionmentioning
confidence: 89%
“…These include studies on substance abuse (Finn, Zeitouni, & Pihl, 1990;Taylor, 2004), harm avoidance (e.g., Grillon & Ameli, 2001), impulsivity and impulsive asociality (e.g., Benning, Patrick, & Iacono, 2005;Verschuere, Crombez, De Clercq, & Koster, 2005), fearlessness (e.g., van Goozen, Snoek, Matthys, van Rossum, & van Engeland, 2004), conduct problems (Quay, 1997), and antisocial personality characteristics (e.g., Babcock, Green, Webb, & Yerington, 2005;Lorber, 2004;Patrick et al, 1993;Patrick, Cuthbert, & Lang, 1994). Among the most widely studied psychophysiological measures are cardiovascular (e.g., heart rate, blood pressure), electrodermal, and startle eyeblink responses.…”
Section: Introductionmentioning
confidence: 99%
“…A second aim of this study was to investigate the effect of habituation on FPLL and its components (FPA and PR). Previous studies indicated that electrodermal and respiratory responses habituate with repeated presentations of concealed information (e.g., Ben-Shakhar et al, 2000;Verschuere et al, 2005). Heart rate has been shown to be more robust to habituation (e.g., Barry, 1977aBarry, ,b, 1978.…”
mentioning
confidence: 97%